11th floor slab, beam and column - WOHA Designs PTE LTD; WEB Structures; BUCG (Brac University, 2023)
This record contains structural contractor shop drawings in perspective of their Request for Approval (RFA) for Brac University new campus project. It contains PDF version of structural contractor shop drawings.